From Society of Sentimentality to Society of Joint Control - M. Yu. Churilin; T. A. Valiulina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes the diagram of demand and supply and identifies median figures, around which demand is formed in case the economic agent presenting it consists of a bigger number of households. The impact of mass media on demand shaping is provided. The article shows how the ad institution influences households and motivates them to buy goods at higher prices. With the help of physicalism analogues of impacts exerted on households are identified and a conclusion is drawn that to analyze economic events it would be useful to apply methods of quantum-relative view of the world instead of traditional methods of mechanicism, which build the foundation of economics. Today’s analogues from physics can enrich tools of economists-theoreticians and provide new interpretations of behaviorist economics, for example why and in what way it is possible to single out a group with certain characteristics from of community of people. This method of putting people in target audience is widely used in advertising even today, which within the frames of globalization economy is becoming a specific tool of shaping society of sentiments. The article uses this term to designate households that under the influence of ads form their expectations about product usefulness. It can give an opportunity to the economic agent that enters the market with product proposal to sell it at the price, whose median figure is higher that the mean product price. In accordance with ideas of physicalistic nature the article demonstrates trends for restructuring national economic space in view of globalization model of economy termination. The author regards economic space as an analogue of electro-magnetic field and the Internet as its extension and he came to the conclusion about changes in methods of influencing households. Sentiment is replaced by methods of joint control that are built by social networks, for instance in bloggers’ community. Such community is often formed by national traits and reputation plays an important role in it.